HUBUNGAN LAMANYA BERMAIN GAME ONLINE DENGAN KELUHAN KELELAHAN MATA PADA SISWA SMA NEGERI 1 DELITUA KEC. DELI TUA KAB. DELI SERDANG - Martha Arizona; rio ferdi yuandra; Pretty Lestari Gultom (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2020)
Users of online games knowdays are increasingly widespread. The duration of playing online games is not recommended more than 4 hours a day. If it exceeds this time, the eyes tend to experience fatigue. Eye fatigue is a dependence on the eyes and is caused by a disturbing sense of vision in the work that requires the ability to see for a long time. In Senior High School 1, students can spend 2-4 hours per day playing online games continuously without adequate rest periods. The aims of the study to determine the relationship of playing online games with complaints of eye fatigue of the students in Senior High School 1 in Delitua. This research used an analytical study with a cross-sectional approach. The sample is 96 students with purposive the sampling technique. Measurements using the Visual Fatigue Index (VFI) questionnaire to measure eye fatigue and the duration of playing online games. The data analysis was performed using the Chi-Square test with a confidence level of 95%. The results of the study on 96 respondents shows that, 58 students were obtained (60.4%) experiencing complaints of eye fatigue. In the light category there were 3 students (3.1%), the medium category was 34 students (35.4%) and the weight category was 21 students (21.9%). The results of the statistical test shows a value of p = 0,000 where p <0.05 means that there is a relationship between playing online games for a long time with complaints of eye fatigue. The suggestions for the community, especially adolescents, school children can pay more attention and limit playing online games so that complaints of eyes fatigue are not often felt and disrupt the health or doing relaxation of the eyes for 15 minutes every one hour to cuting the chain of eyes fatigue such as closing the eyes or pointing at other objects.